Open social scholarship in action. (5th August 2020) - El Khatib, Randa; Arbuckle, Alyssa; Winter, Caroline; Siemens, Ray; ,
Abstract: Open social scholarship highlights outreach and partnerships by emphasizing community-driven initiatives in an attempt to bridge the gap between the practices of the university and the goals of the community. Over the last few years, the Electronic Textual Cultures Lab at the University of Victoria has introduced a number of initiatives to this end, including the Open Knowledge Program and Open Scholarship Awards. In describing these initiatives, the article engages the larger framework of community engagement and public-facing scholarship. The guiding questions for this article and our work more broadly are: how can we productively put open social scholarship into practice? What type of scholarship is considered public facing? What is the best practice around co-creating knowledge in the humanities with communities that are academic-aligned or non-academic?